Survival time to first antenatal care visit and its predictors among women in Ethiopia. - Abdu Seid (Public Library of Science (PLoS), 2021)
Background First-trimester pregnancy stage is the fastest developmental period of the fetus, in which all organs become well developed and need special care. Yet, many women make their first antenatal visit with the pregnancy already compromised due to fetomaternal complications. This study aimed to fill this dearth using the 2016 national representative data set to augment early antenatal care visits in Ethiopia. Methods A cross-sectional study design using the 2016 Ethiopia Demographic and Health Survey (EDHS) data set. Kaplan-Meir estimate was used to explain the median survival time of the timing of the first ANC visit. Multivariate Cox-proportional hazard regression analysis was performed to identify the factors related to the timing of the first ANC visit. Adjusted hazard ratios (AHR) with a 95% Confidence interval (CI) plus a p-value of < 0.05 were considered to declare a statistically significant association. Results Data for 4666 study participants who had ANC follow-up history during pregnancy were included in the study and analyzed. The overall median survival time in this study was seven months. The timing of the first ANC visit was shorter by 2.5 times (AHR: 2.5; 95% CI: 2.34-3.68), 4.3 times (AHR: 4.3; 95% CI: 2.2-7.66), 4.8 times (AHR: 4.8, 95% CI: 4.56-10.8) among women who attended primary, secondary, and higher education as compared with non-educated one. Similarly, women who were residing in urban areas had 3.6 times (AHR: 3.6; 95% CI: 2.7-4.32) shorter timing of first ANC visit than rural residents. Furthermore, the timing of the first visit among the richest women was 3.2 times (AHR: 3.2; 95% CI: 2.5-9.65) shorter than the poorest women. Conclusion The median survival time of the first ANC visit was seven months. The timing of the first ANC was longer among younger, poorer women, those who had no access to media, who considered distances as a big challenge to reach a health facility and, those with no education. Therefore, health care providers and community health workers should provide health education to create community awareness regarding the timing of the first ANC visit.